Interviewing the Digital Materialities of Posthuman Inquiry: Decoding the encoding of research practices - Adams, Catherine; Thompson, Terrie Lynn (Proceedings of the International Conference on Networked Learning, 2014)
Have you considered how the many things assisting you with your research—digital recorders, computer assisted qualitative data analysis software (CAQDAS) or even Google Scholar—may also be silently shaping scholarly practices? In this paper, we interrogate the networked, digital landscape of everyday qualitative research practices by unraveling several examples taken from recent empirical studies in educational and social science. Our disentangling and decoding of the digital materialities of qualitative inquiry involves “interviewing” several digital objects—a recording device, a digital camera, an iPod, and a software program—that were recruited at different stages of several contemporary research projects. We deploy Adams and Thompson’s (2011) heuristics for interviewing nonhuman or “thingly” research participants, and apply these to the digital things of qualitative research practices. We suggest that these digital entities—“coded materialities” —participate as co-researchers that transform, extend and support but also deform, disrupt and circumscribe research practice and knowledge construction, and inevitably introduce new tensions and contradictions. Counterpointing two approaches to describing our enacted and pre-objective material worlds—Actor Network Theory and phenomenology, we usher into view some of the hidden and coded materialities of research practice, and glimpse unexpected realities enacted. Such immersive entanglements ultimately raise new questions about the posthumanist fluencies demanded in social science research practice. One such fluency is reckoning with how our agency as researchers is increasing shared, distributed and supported by digital technologies. Our entanglements with coded materialities introduce new ethical tensions and responsibilities into research practice. Second, new fluencies may also be called into play as the researcher’s work is subject to both deskilling and up-skilling as various technologies sit alongside researchers as co-researchers. Third, when data is viewed as lively, relational and mobile, new enactments of data are possible. Learning to work with these complex data circulations is another posthuman research digital fluency. Fourth, the scale, mobility, and spatial arrangements of the research process are being radically reconfigured as increasingly public and fragmented; these new arrangements bring both tensions and opportunities to be. Finally, with data being frozen and thawed in the fluidity of digitized research spaces, researchers must be attentive to how and what data is being included and excluded. We conclude by suggesting that researchers “build in” opportunities to regularly query the digital tools of their trade.